2021
DOI: 10.1186/s12957-021-02214-5
|View full text |Cite
|
Sign up to set email alerts
|

Loco-regional recurrence trend and prognosis in young women with breast cancer according to molecular subtypes: analysis of 1099 cases

Abstract: Background The number of young patients diagnosed with breast cancer is on the rise. We studied the rate trend of local recurrence (LR) and regional recurrence (RR) in young breast cancer (YBC) patients and outcomes among these patients based on molecular subtypes. Methods A retrospective cohort study was conducted based on data from Tianjin Medical University Cancer Institute and Hospital for patients ≤ 35 years of age with pathologically confirme… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
18
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 48 publications
3
18
1
Order By: Relevance
“…Globally, breast cancer is the most frequently diagnosed cancer and a major cause of death in women worldwide (1). Recurrence of breast cancer cells occurs in a significant number of patients with a recent meta-analysis showing that the overall 5-year rates for distant metastasis, regional recurrence, and local recurrence in <35-year-old breast cancer patients were 16.6%, 5.1%, and 6.7%, respectively (2). Currently, tumor-node-metastasis staging is implemented to stratify patients; yet, patients within the same stage still can show a different clinical outcome.…”
Section: Introductionmentioning
confidence: 99%
“…Globally, breast cancer is the most frequently diagnosed cancer and a major cause of death in women worldwide (1). Recurrence of breast cancer cells occurs in a significant number of patients with a recent meta-analysis showing that the overall 5-year rates for distant metastasis, regional recurrence, and local recurrence in <35-year-old breast cancer patients were 16.6%, 5.1%, and 6.7%, respectively (2). Currently, tumor-node-metastasis staging is implemented to stratify patients; yet, patients within the same stage still can show a different clinical outcome.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, molecular subtypes along with the four immunohistochemical factors are employed as a guide for targeted treatment, including hormonal therapy, anti-Her2 agent, and cytotoxic therapy [ 8 , 10 , 11 ]. Moreover, differences in prognosis among different subtypes of breast cancer also existed [ 12 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, our study demonstrated that patients with TNBC or HER2-positive subtype who met the Z0011 criteria received more ALND than those with other subtypes. As TNBC or HER2-positive tumors are strong predictors of disease recurrence, a more aggressive surgical management for axilla seems to have been carried out [ 27 , 28 ].…”
Section: Discussionmentioning
confidence: 99%